Transparent Conductive Film

By adding krypton gas and indium-containing conductive oxides to the light-conducting conductive layer of the transparent conductive film, the problem of low etching rate of the light-conducting conductive layer in the prior art is solved, and higher etching rate and conductivity are achieved, and manufacturing efficiency is improved.

JP7654592B2Active Publication Date: 2025-04-01NITTO DENKO CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2022078431
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-12-02
Filing Date
2022-05-11
Publication Date
2025-04-01
Estimated Expiration
2041-03-18

AI Technical Summary

Technical Problem

The existing transparent conductive film has a low etching rate of the light-conducting conductive layer during the etching process, resulting in low equipment manufacturing efficiency.

Method used

Krypton gas (Kr) is added to the light-conducting conductive layer of the transparent conductive film, and conductive oxides containing indium are used to optimize the structure and composition of the conductive layer to improve its conductivity and etching rate.

Benefits of technology

By increasing krypton gas and indium-containing conductive oxides, the etching rate and conductivity of the light-conducting conductive layer are significantly improved, and the efficiency of equipment manufacturing is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007654592000002
    Figure 0007654592000002
  • Figure 0007654592000003
    Figure 0007654592000003
  • Figure 0007654592000004
    Figure 0007654592000004
Patent Text Reader

Abstract

A transparent conductive film suitable for realizing a high etching rate in a light-transmitting conductive layer is provided. The transparent conductive film X of the present invention comprises a transparent substrate 10 and a light-transmitting conductive layer 20 in this order in the thickness direction D. The light-transmitting conductive layer 20 contains krypton and has a thickness of 2.8×10 -4 The light-transmitting conductive layer 20 has a resistivity of less than Ω·cm. The light-transmitting conductive layer 20 has a hole mobility μ (cm 2 / V s) and carrier density n×10 19 (cm -3 ) and the ratio of n to μ is 4 or greater.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a transparent conductive film. [Background technology]

[0002] Conventionally, a transparent conductive film having a transparent substrate film and a transparent conductive layer (light-transmitting conductive layer) in order in the thickness direction has been known. The light-transmitting conductive layer is used as a conductive film for patterning transparent electrodes in various devices such as liquid crystal displays, touch panels, and optical sensors. The light-transmitting conductive layer is formed, for example, by forming a film of a conductive oxide on a substrate film by a sputtering method. In the sputtering method, an inert gas such as argon is conventionally used as a sputtering gas for colliding with a target (a film-forming material supply material) to eject atoms on the target surface. A technology related to such a transparent conductive film is described, for example, in Patent Document 1 below. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2017-71850 A Summary of the Invention [Problem to be solved by the invention]

[0004] The light-transmitting conductive layer of the transparent conductive film is patterned by etching the light-transmitting conductive layer through a predetermined etching mask. However, the transparent conductive film of Patent Document 1 has a problem that the etching rate of the light-transmitting conductive layer is slow in the etching process. A slow etching rate of the light-transmitting conductive layer in the transparent conductive film is undesirable from the viewpoint of the efficiency of the device manufacturing process in which the transparent conductive film is used.

[0005] The present invention provides a transparent conductive film suitable for achieving a high etching rate in a light-transmitting conductive layer. [Means for solving the problem]

[0006] The present invention [1] comprises a transparent substrate and a light-transmitting conductive layer in this order in the thickness direction, and the light-transmitting conductive layer contains krypton and has a density of 2.8×10 -4 The light-transmitting conductive layer has a resistivity of less than Ω·cm and a hole mobility μ(cm 2 / V s) and carrier density n×10 19 (cm -3 ) and the ratio of n to μ is 4 or greater.

[0007] The present invention [2] includes the transparent conductive film according to the above [1], in which the light-transmitting conductive layer contains an indium-containing conductive oxide.

[0008] The present invention [3] is a method for manufacturing a semiconductor device having a hole mobility of 5 cm 2 / V·s or more 40cm 2 / V·s or less.

[0009] The present invention [4] is a method for manufacturing a semiconductor device having a carrier density of 100×10 19 cm -3 Over 170×10 19 cm -3 The present invention includes a transparent conductive film according to any one of the above [1] to [3], which is as follows:

[0010] The present invention [5] includes the transparent conductive film according to any one of the above [1] to [4], in which the light-transmitting conductive layer is patterned.

[0011] The present invention [6] is characterized in that the light-transmitting conductive layer has a thickness of 2.2×10 -4 The transparent conductive film according to any one of the above [1] to [5] has a resistivity of less than Ω·cm. Effect of the Invention

[0012] The transparent conductive film of the present invention is characterized in that the light-transmitting conductive layer contains krypton and has a surface area of ​​2.8×10 -4 In addition, in the transparent conductive film of the present invention, the light-transmitting conductive layer has a hole mobility μ(cm 2 / V s) and carrier density n×10 19 (cm -3 ), the ratio of n to μ is equal to or greater than 4. Therefore, the transparent conductive film of the present invention is suitable for achieving a high etching rate in the light-transmitting conductive layer. [Brief description of the drawings]

[0013] [Figure 1] 1 is a schematic cross-sectional view of one embodiment of a transparent conductive film of the present invention. [Diagram 2] A method for producing a transparent conductive film shown in Fig. 1 is shown. Fig. 2A shows a step of preparing a resin film, Fig. 2B shows a step of forming a functional layer on the resin film, Fig. 2C shows a step of forming a light-transmitting conductive layer on the functional layer, and Fig. 2D shows a step of crystallizing the light-transmitting conductive layer. [Diagram 3] This illustrates a case where the light-transmitting conductive layer in the transparent conductive film shown in FIG. 1 is patterned. [Figure 4] 1 is a graph showing the relationship between the amount of oxygen introduced when forming a light-transmitting conductive layer by a sputtering method and the resistivity of the formed light-transmitting conductive layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] 1 is a schematic cross-sectional view of a transparent conductive film X, which is one embodiment of the transparent conductive film of the present invention. The transparent conductive film X includes a transparent substrate 10 and a light-transmitting conductive layer 20, in this order, toward one side in a thickness direction D. The transparent conductive film X has a shape that spreads in a direction (plane direction) perpendicular to the thickness direction D. The transparent conductive film X is an element included in a touch sensor device, a light control element, a photoelectric conversion element, a heat ray control member, an antenna member, an electromagnetic wave shielding member, a lighting device, an image display device, and the like.

[0015] In this embodiment, the transparent substrate 10 includes a resin film 11 and a functional layer 12, in this order, toward one side in a thickness direction D. The transparent substrate 10 has a shape that extends in a direction perpendicular to the thickness direction D (plane direction).

[0016] The resin film 11 is a transparent resin film having flexibility. Examples of the material of the resin film 11 include polyester resin, polyolefin resin, acrylic resin, polycarbonate resin, polyethersulfone resin, polyarylate resin, melamine resin, polyamide resin, polyimide resin, cellulose resin, and polystyrene resin. Examples of the polyester resin include polyethylene terephthalate (PET), polybutylene terephthalate, and polyethylene naphthalate. Examples of the polyolefin resin include polyethylene, polypropylene, and cycloolefin polymer (COP). Examples of the acrylic resin include polymethacrylate. Examples of the acrylic resin include polymethacrylate. As the material of the resin film 11, for example, from the viewpoint of transparency and strength, a polyolefin resin is preferably used, and more preferably a COP is used.

[0017] The surface of the resin film 11 facing the functional layer 12 may be subjected to a surface modification treatment. Examples of the surface modification treatment include corona treatment, plasma treatment, ozone treatment, primer treatment, glow treatment, and coupling agent treatment.

[0018] The thickness of the resin film 11 is preferably 1 μm or more, more preferably 10 μm or more, and even more preferably 30 μm or more. The thickness of the resin film 11 is preferably 300 μm or less, more preferably 200 μm or less, even more preferably 100 μm or less, and particularly preferably 75 μm or less. These configurations regarding the thickness of the resin film 11 are suitable for ensuring the handleability of the transparent conductive film X.

[0019] The total light transmittance (JIS K 7375-2008) of the resin film 11 is preferably 60% or more, more preferably 80% or more, and even more preferably 85% or more. Such a configuration is suitable for ensuring the transparency required of the transparent conductive film X when the transparent conductive film X is provided in a touch sensor device, a light control element, a photoelectric conversion element, a heat ray control member, an antenna member, an electromagnetic wave shielding member, a lighting device, an image display device, and the like. The total light transmittance of the resin film 11 is, for example, 100% or less.

[0020] In this embodiment, the functional layer 12 is located on one surface of the resin film 11 in the thickness direction D. In this embodiment, the functional layer 12 is a hard coat layer that makes it difficult for scratches to form on the exposed surface (the upper surface in FIG. 1 ) of the light-transmitting conductive layer 20.

[0021] The hard coat layer is a cured product of a curable resin composition. Examples of the resin contained in the curable resin composition include polyester resin, acrylic resin, urethane resin, amide resin, silicone resin, epoxy resin, and melamine resin. Examples of the curable resin composition include an ultraviolet-curable resin composition and a thermosetting resin composition. Since the curable resin composition can be cured without high-temperature heating, and therefore is useful for improving the production efficiency of the transparent conductive film X, an ultraviolet-curable resin composition is preferably used as the curable resin composition. Specific examples of the ultraviolet-curable resin composition include the composition for forming a hard coat layer described in JP 2016-179686 A.

[0022] The surface of the functional layer 12 facing the light-transmitting conductive layer 20 may be subjected to a surface modification treatment. Examples of the surface modification treatment include corona treatment, plasma treatment, ozone treatment, primer treatment, glow treatment, and coupling agent treatment.

[0023] The thickness of the functional layer 12 as a hard coat layer is preferably 0.1 μm or more, more preferably 0.5 μm or more, and even more preferably 1 μm or more. Such a configuration is suitable for achieving sufficient scratch resistance in the light-transmitting conductive layer 20. From the viewpoint of ensuring the transparency of the functional layer 12, the thickness of the functional layer 12 as a hard coat layer is preferably 10 μm or less, more preferably 5 μm or less, and even more preferably 3 μm or less.

[0024] The thickness of the transparent substrate 10 is preferably 1 μm or more, more preferably 10 μm or more, even more preferably 15 μm or more, and particularly preferably 30 μm or more. The thickness of the transparent substrate 10 is preferably 310 μm or less, more preferably 210 μm or less, even more preferably 110 μm or less, and particularly preferably 80 μm or less. These configurations regarding the thickness of the transparent substrate 10 are suitable for ensuring the handleability of the transparent conductive film X.

[0025] The total light transmittance (JIS K 7375-2008) of the transparent substrate 10 is preferably 60% or more, more preferably 80% or more, and even more preferably 85% or more. Such a configuration is suitable for ensuring the transparency required of the transparent conductive film X when the transparent conductive film X is provided in a touch sensor device, a light control element, a photoelectric conversion element, a heat ray control member, an antenna member, an electromagnetic wave shielding member, a lighting device, an image display device, and the like. The total light transmittance of the transparent substrate 10 is, for example, 100% or less.

[0026] In this embodiment, the light-transmitting conductive layer 20 is located on one surface of the transparent substrate 10 in the thickness direction D. The light-transmitting conductive layer 20 is a crystalline film that has both light transparency and conductivity.

[0027] The light-transmitting conductive layer 20 is a layer formed from a light-transmitting conductive material. The light-transmitting conductive material contains, for example, a conductive oxide as a main component.

[0028] Examples of the conductive oxide include metal oxides containing at least one metal or metalloid selected from the group consisting of In, Sn, Zn, Ga, Sb, Ti, Si, Zr, Mg, Al, Au, Ag, Cu, Pd, and W. Specifically, examples of the conductive oxide include indium-containing conductive oxides and antimony-containing conductive oxides. Examples of the indium-containing conductive oxide include indium tin composite oxide (ITO), indium zinc composite oxide (IZO), indium gallium composite oxide (IGO), and indium gallium zinc composite oxide (IGZO). Examples of the antimony-containing conductive oxide include antimony tin composite oxide (ATO). From the viewpoint of achieving high transparency and good conductivity, the conductive oxide is preferably an indium-containing conductive oxide, and more preferably ITO. This ITO may contain a metal or metalloid other than In and Sn in an amount less than the respective contents of In and Sn.

[0029] When ITO is used as the conductive oxide, the ratio of the content of tin oxide to the total content of indium oxide (In2O3) and tin oxide (SnO2) in the light-transmitting conductive layer 20 (tin oxide content) is preferably 1 mass% or more, more preferably 3 mass% or more, even more preferably 5 mass% or more, and particularly preferably 7 mass% or more. Such a configuration is suitable for ensuring the durability of the light-transmitting conductive layer 20. In addition, from the viewpoint of obtaining a light-transmitting conductive layer 20 that is easily crystallized by heating, the tin oxide content is preferably 15 mass% or less, more preferably 13 mass% or less, and even more preferably 12 mass% or less. The above content of tin oxide is obtained from an XPS spectrum measured by X-ray photoelectron spectroscopy for the measurement object.

[0030] The tin oxide content in the light-transmitting conductive layer 20 may be non-uniform in the thickness direction D. For example, the light-transmitting conductive layer 20 may include a first layer having a relatively high tin oxide content and a second layer having a relatively low tin oxide content, in this order from the transparent substrate 10 side. The tin oxide content in the first layer is preferably 5% by mass or more, more preferably 8% by mass or more. The tin oxide content in the first layer is preferably 15% by mass or less, more preferably 13% by mass or less. The tin oxide content in the second layer is preferably 0.5% by mass or more, more preferably 2% by mass or more. The tin oxide content in the second layer is preferably 8% by mass or less, more preferably 5% by mass or less. The ratio of the thickness of the first layer to the thickness of the light-transmitting conductive layer 20 is preferably 50% or more, more preferably 60% or more, and even more preferably 70% or more. Furthermore, the ratio of the thickness of the second layer to the thickness of the light-transmitting conductive layer 20 is preferably 50% or less, more preferably 40% or less, and even more preferably 30% or less.

[0031] The light-transmitting conductive layer 20 contains krypton (Kr) as rare gas atoms. In this embodiment, the rare gas atoms in the light-transmitting conductive layer 20 are derived from rare gas atoms used as a sputtering gas in a sputtering method described later. In this embodiment, the light-transmitting conductive layer 20 is a film (sputtered film) formed by a sputtering method.

[0032] The light-transmitting conductive layer 20 containing Kr is suitable for realizing low resistance in the light-transmitting conductive layer 20. In addition, this configuration is suitable for realizing a high etching rate when the light-transmitting conductive layer 20 is etched, for example, for patterning. The presence or absence of Kr in the light-transmitting conductive layer 20 is identified, for example, by X-ray fluorescence analysis, which will be described later in relation to the examples.

[0033] The content of Kr in the light-transmitting conductive layer 20 is, for example, 0.5 atomic % or less, preferably 0.3 atomic % or less, and more preferably 0.2 atomic % or less, in the entire region in the thickness direction D. Such a configuration is suitable for realizing good crystal growth and forming large crystal grains when the amorphous light-transmitting conductive layer (light-transmitting conductive layer 20' described below) is crystallized by heating to form the light-transmitting conductive layer 20 in the manufacturing process of the transparent conductive film X, and is therefore suitable for obtaining a light-transmitting conductive layer 20 with low resistance (the larger the crystal grains in the light-transmitting conductive layer 20, the lower the resistance of the light-transmitting conductive layer 20). The content of Kr in the light-transmitting conductive layer 20 is, for example, 0.0001 atomic % or more in the entire region in the thickness direction D.

[0034] The Kr content in the light-transmitting conductive layer 20 may be non-uniform in the thickness direction D. For example, in the thickness direction D, the Kr content may gradually increase or decrease as it moves away from the transparent substrate 10. Alternatively, in the thickness direction D, a partial region in which the Kr content gradually increases as it moves away from the transparent substrate 10 may be located on the transparent substrate 10 side, and a partial region in which the Kr content gradually decreases as it moves away from the transparent substrate 10 may be located on the opposite side to the transparent substrate 10. Alternatively, in the thickness direction D, a partial region in which the Kr content gradually decreases as it moves away from the transparent substrate 10 may be located on the transparent substrate 10 side, and a partial region in which the Kr content gradually increases as it moves away from the transparent substrate 10 may be located on the opposite side to the transparent substrate 10.

[0035] The light-transmitting conductive layer 20 preferably contains only Kr as rare gas atoms. Such a configuration is preferable from the viewpoint of realizing low resistance in the light-transmitting conductive layer 20. In addition, this configuration is preferable from the viewpoint of realizing a high etching rate when the light-transmitting conductive layer 20 is etched, for example, for patterning.

[0036] When the light-transmitting conductive layer 20 contains rare gas atoms other than Kr, examples of the rare gas atoms other than Kr include argon (Ar) and xenon (Xe). From the viewpoint of reducing the manufacturing cost of the transparent conductive film X, the light-transmitting conductive layer 20 preferably does not contain Xe.

[0037] The content of rare gas atoms (including Kr) in the light-transmitting conductive layer 20 is, for example, 0.5 atomic % or less, preferably 0.3 atomic % or less, and more preferably 0.2 atomic % or less, in the entire region in the thickness direction D. Such a configuration is suitable for realizing good crystal growth and forming large crystal grains when the amorphous light-transmitting conductive layer is crystallized by heating to form the light-transmitting conductive layer 20 in the manufacturing process of the transparent conductive film X, and is therefore suitable for obtaining a light-transmitting conductive layer 20 with low resistance. The content of rare gas atoms in the light-transmitting conductive layer 20 is, for example, 0.0001 atomic % or more in the entire region in the thickness direction D.

[0038] The thickness of the light-transmitting conductive layer 20 is, for example, 10 nm or more, preferably 25 nm or more, more preferably 30 nm or more, even more preferably 35 nm or more, and particularly preferably 40 nm or more. Such a configuration is suitable for reducing the resistance of the light-transmitting conductive layer 20. The thickness of the light-transmitting conductive layer 20 is, for example, 1000 nm or less, preferably less than 300 nm, more preferably 250 nm or less, even more preferably 200 nm or less, even more preferably 160 nm or less, particularly preferably less than 150 nm, and most preferably 148 nm or less. Such a configuration is suitable for reducing the compressive residual stress of the light-transmitting conductive layer 20 and suppressing warping of the transparent conductive film X.

[0039] The total light transmittance (JIS K 7375-2008) of the light-transmitting conductive layer 20 is preferably 60% or more, more preferably 80% or more, and even more preferably 85% or more. Such a configuration is suitable for ensuring the transparency of the light-transmitting conductive layer 20. The total light transmittance of the light-transmitting conductive layer 20 is, for example, 100% or less.

[0040] The surface resistance of the light-transmitting conductive layer 20 is, for example, 200Ω / □ or less, preferably 70Ω / □ or less, more preferably 55Ω / □ or less, even more preferably 50Ω / □ or less, and particularly preferably 45Ω / □ or less. The surface resistance of the light-transmitting conductive layer 20 is, for example, 1Ω / □ or more. These configurations regarding the surface resistance are suitable for ensuring the low resistance required of the light-transmitting conductive layer 20 when the transparent conductive film X is provided in a touch sensor device, a light control element, a photoelectric conversion element, a heat ray control member, an antenna member, an electromagnetic wave shielding member, a lighting device, an image display device, and the like. The surface resistance can be measured by a four-terminal method in accordance with JIS K7194.

[0041] The resistivity of the light-transmitting conductive layer 20 is 2.8×10 -4 Less than Ω cm, preferably less than 2.2×10 -4 Ω cm or less, preferably 2×10 -4 Ω cm or less, more preferably 1.8×10 -4 Ω cm or less, particularly preferably 1.7×10 -4 The specific resistance of the light-transmitting conductive layer 20 is, for example, 0.1×10 -4 The resistivity is Ω·cm or more. These configurations regarding the resistivity are suitable for ensuring the low resistivity required for the light-transmitting conductive layer 20 when the transparent conductive film X is provided in a touch sensor device, a light control element, a photoelectric conversion element, a heat ray control member, an antenna member, an electromagnetic wave shielding member, a lighting device, an image display device, and the like. The resistivity is calculated by multiplying the surface resistance by the thickness.

[0042] The hole mobility in the light-transmitting conductive layer 20 is preferably 5 cm 2 / V·s or more, preferably 10 cm 2 / V·s or more, preferably 20cm 2 The hole mobility of the light-transmitting conductive layer 20 is preferably 40 cm 2 / V·s or less, preferably 35 cm 2 / V·s or less, and more preferably 30 cm 2 / V·s or less. The hole mobility can be adjusted, for example, by adjusting the Kr content in the light-transmitting conductive layer 20 and adjusting various conditions when sputtering the amorphous light-transmitting conductive layer (light-transmitting conductive layer 20' described below) that is converted into the light-transmitting conductive layer 20 by heating. Such conditions include, for example, the temperature of the base (transparent substrate 10 in this embodiment) on which the amorphous light-transmitting conductive layer is formed, and the sputtering output on the substrate side (transparent substrate 10 in this embodiment). The hole mobility can also be adjusted by adjusting the surface properties, such as the surface shape of the base (surface properties of the functional layer 12 in this embodiment) on which the amorphous light-transmitting conductive layer is formed.

[0043] The carrier density in the light-transmitting conductive layer 20 is preferably 100×10 19 cm -3 More preferably, 120×10 19 cm -3 The carrier density in the light-transmitting conductive layer 20 is preferably 170×10 19 cm -3 Less than or equal to 150×10 19 cm -3 The carrier density can be adjusted, for example, by adjusting the Kr content in the light-transmitting conductive layer 20 and by adjusting various conditions when sputtering the amorphous light-transmitting conductive layer (light-transmitting conductive layer 20' described below) that is converted into the light-transmitting conductive layer 20 by heating. Such conditions include, for example, the temperature of the base (transparent substrate 10 in this embodiment) on which the amorphous light-transmitting conductive layer is formed, and the amount of oxygen introduced into the film formation chamber. The carrier density can also be adjusted by adjusting the surface properties of the base (surface properties of the functional layer 12 in this embodiment) on which the amorphous light-transmitting conductive layer is formed.

[0044] The hole mobility of the light-transmitting conductive layer 20 is μ(cm 2 / V s), and the carrier density of the light-transmitting conductive layer 20 is n×10 19 cm -3In this case, the ratio of n to μ (n / μ) is 4 or more, preferably 4.2 or more, more preferably 4.4 or more, even more preferably 5 or more, and particularly preferably 6 or more. Such a configuration is suitable for achieving a high etching rate in the light-transmitting conductive layer 20. From the viewpoint of achieving both a high etching rate and low resistance in the light-transmitting conductive layer 20, the ratio of n to μ is, for example, 20 or less, preferably 10 or less, and more preferably less than 6.2.

[0045] Whether the light-transmitting conductive layer is crystalline can be determined, for example, as follows. First, the light-transmitting conductive layer (in the case of the transparent conductive film X, the light-transmitting conductive layer 20 on the transparent substrate 10) is immersed in hydrochloric acid with a concentration of 5% by mass at 20° C. for 15 minutes. Next, the light-transmitting conductive layer is washed with water and then dried. Next, the resistance (inter-terminal resistance) between a pair of terminals separated by a distance of 15 mm is measured on the exposed flat surface of the light-transmitting conductive layer (in the case of the transparent conductive film X, the surface of the light-transmitting conductive layer 20 opposite the transparent substrate 10). In this measurement, if the inter-terminal resistance is 10 kΩ or less, the light-transmitting conductive layer is crystalline.

[0046] The transparent conductive film X is produced, for example, as follows.

[0047] First, as shown in FIG. 2A, a resin film 11 is prepared.

[0048] 2B, a functional layer 12 is formed on one surface of the resin film 11 in the thickness direction D. By forming the functional layer 12 on the resin film 11, a transparent substrate 10 is produced.

[0049] The functional layer 12 as a hard coat layer can be formed by applying a curable resin composition onto the resin film 11 to form a coating film, and then curing the coating film. When the curable resin composition contains an ultraviolet-curable resin, the coating film is cured by ultraviolet irradiation. When the curable resin composition contains a thermosetting resin, the coating film is cured by heating.

[0050] The exposed surface of the functional layer 12 formed on the resin film 11 is subjected to a surface modification treatment as necessary. When a plasma treatment is used as the surface modification treatment, argon gas, for example, is used as an inert gas. The discharge power in the plasma treatment is, for example, 100 W or more and, for example, 500 W or less.

[0051] Next, as shown in Fig. 2C, an amorphous light-transmitting conductive layer 20' is formed on the transparent substrate 10 (film formation process). Specifically, a material is formed on the functional layer 12 of the transparent substrate 10 by a sputtering method to form an amorphous light-transmitting conductive layer 20'. The light-transmitting conductive layer 20' is an amorphous film that has both light transparency and conductivity (the light-transmitting conductive layer 20' is converted into a crystalline light-transmitting conductive layer 20 by heating in a crystallization process described later).

[0052] In the sputtering method, it is preferable to use a sputtering deposition apparatus capable of performing a film formation process by a roll-to-roll method. When using a sputtering deposition apparatus of the roll-to-roll method in the manufacture of the transparent conductive film X, a material is deposited on the long transparent substrate 10 while the transparent substrate 10 is traveling from a pay-out roll to a take-up roll provided in the apparatus, to form the light-transmitting conductive layer 20'. In addition, in the sputtering method, a sputtering deposition apparatus having one deposition chamber may be used, or a sputtering deposition apparatus having multiple deposition chambers arranged in order along the traveling path of the transparent substrate 10 may be used (when forming the light-transmitting conductive layer 20' including the above-mentioned first layer and second layer, a sputtering deposition apparatus having two or more deposition chambers is used).

[0053] Specifically, in the sputtering method, a sputtering gas (inert gas) is introduced into a film-forming chamber under vacuum conditions, while a negative voltage is applied to a target placed on a cathode in the film-forming chamber. This generates a glow discharge to ionize gas atoms, and the gas ions collide with the target surface at high speed to eject target material from the target surface, and the ejected target material is deposited on the functional layer 12 of the transparent substrate 10.

[0054] The material of the target placed on the cathode in the film formation chamber is the conductive oxide described above for the light-transmitting conductive layer 20, preferably an indium-containing conductive oxide, and more preferably ITO. When ITO is used, the ratio of the tin oxide content to the total content of tin oxide and indium oxide in the ITO is preferably 1 mass% or more, more preferably 3 mass% or more, even more preferably 5 mass% or more, particularly preferably 7 mass% or more, and is preferably 15 mass% or less, more preferably 13 mass% or less, and even more preferably 12 mass% or less.

[0055] The sputtering method is preferably a reactive sputtering method, in which a reactive gas is introduced into the deposition chamber in addition to the sputtering gas.

[0056] When forming a light-transmitting conductive layer 20' containing Kr throughout the thickness direction D, the gas introduced into the film formation chamber contains Kr as a sputtering gas and oxygen as a reactive gas. The sputtering gas may contain an inert gas other than Kr. Examples of the inert gas other than Kr include rare gas atoms other than Kr. Examples of the rare gas atoms include Ar and Xe. When the sputtering gas contains an inert gas other than Kr, the content is preferably 5% by volume or less, more preferably 3% by volume or less.

[0057] In the reactive sputtering method, the ratio of the amount of oxygen introduced to the total amount of sputtering gas and oxygen introduced into the film formation chamber is, for example, 0.1 flow % or more and, for example, 5 flow % or less.

[0058] The air pressure in the film formation chamber during film formation by sputtering (sputter film formation) is, for example, 0.02 Pa or more and, for example, 1 Pa or less.

[0059] The temperature of the transparent substrate 10 during sputtering deposition is, for example, 100° C. or lower, preferably 50° C. or lower, more preferably 30° C. or lower, and is, for example, −20° C. or higher, preferably −10° C. or higher, more preferably −7° C. or higher.

[0060] Examples of the power source for applying voltage to the target include a DC power source, an AC power source, an MF power source, and an RF power source. The power source may be a combination of a DC power source and an RF power source. The discharge voltage during sputtering is, for example, 200V or more and, for example, 400V or less.

[0061] In the present manufacturing method, next, as shown in FIG. 2D, the light-transmitting conductive layer 20 is converted (crystallized) from amorphous to crystalline by heating (crystallization step). Examples of heating means include an infrared heater and an oven. From the viewpoint of ensuring a high crystallization rate, the heating temperature is, for example, 100° C. or higher, and preferably 120° C. or higher. From the viewpoint of suppressing the influence of heating on the transparent substrate 10, the heating temperature is, for example, 200° C. or lower, preferably 180° C. or lower, more preferably 170° C. or lower, and even more preferably 165° C. or lower. The heating time is, for example, 6 hours or lower, preferably 200 minutes or lower, more preferably 150 minutes or lower, and even more preferably 90 minutes or lower, and also, for example, 1 minute or more, preferably 5 minutes or more.

[0062] In this manner, the transparent conductive film X is produced.

[0063] The light-transmitting conductive layer 20 in the transparent conductive film X may be patterned as shown in FIG. 3. The light-transmitting conductive layer 20 can be patterned by etching the light-transmitting conductive layer 20 through a predetermined etching mask. The patterning of the light-transmitting conductive layer 20 may be performed before or after the above-mentioned crystallization step. The patterned light-transmitting conductive layer 20 functions as, for example, a wiring pattern.

[0064] As described above, the transparent conductive film X has a light-transmitting conductive layer 20 on a transparent substrate 10 that contains krypton and has a surface area of ​​2.8×10 -4 In addition, the light-transmitting conductive layer has a hole mobility μ(cm 2 / V s) and the carrier density is n×10 19 (cm -3 ), the ratio of n to μ (n / μ) is 4 or more, preferably 4.2 or more, more preferably 4.4 or more, even more preferably 5 or more, and particularly preferably 6 or more.

[0065] Such a configuration of the transparent conductive film X is suitable for achieving a high etching rate in the light-transmitting conductive layer 20. Specific examples are as shown in the examples and comparative examples described below.

[0066] In the transparent conductive film X, the functional layer 12 may be an adhesion improving layer for realizing high adhesion of the light-transmitting conductive layer 20 to the transparent substrate 10. The configuration in which the functional layer 12 is an adhesion improving layer is suitable for ensuring adhesion between the transparent substrate 10 and the light-transmitting conductive layer 20.

[0067] The functional layer 12 may be an index-matching layer for adjusting the reflectance of the surface (one surface in the thickness direction D) of the transparent substrate 10. The configuration in which the functional layer 12 is an index-matching layer is suitable for making the pattern shape of the light-transmitting conductive layer 20 on the transparent substrate 10 less visible when the light-transmitting conductive layer 20 on the transparent substrate 10 is patterned.

[0068] The functional layer 12 may be a peelable functional layer for making it practical to peel the light-transmitting conductive layer 20 from the transparent substrate 10. The configuration in which the functional layer 12 is a peelable functional layer is suitable for peeling the light-transmitting conductive layer 20 from the transparent substrate 10 and transferring the light-transmitting conductive layer 20 to another member.

[0069] The functional layer 12 may be a composite layer in which a plurality of layers are arranged in the thickness direction D. The composite layer preferably includes two or more layers selected from the group consisting of a hard coat layer, an adhesion improving layer, a refractive index adjustment layer, and a release functional layer. Such a configuration is suitable for the functional layer 12 to exhibit the above-mentioned functions of each selected layer in a composite manner. In a preferred embodiment, the functional layer 12 includes an adhesion improving layer, a hard coat layer, and a refractive index adjustment layer on the resin film 11, in this order toward one side of the thickness direction D. In another preferred embodiment, the functional layer 12 includes a release functional layer, a hard coat layer, and a refractive index adjustment layer on the resin film 11, in this order toward one side of the thickness direction D.

[0070] The transparent conductive film X is attached to an article and, if necessary, patterned before use. The transparent conductive film X is attached to the article, for example, via an adhesive functional layer.

[0071] Examples of the article include an element, a member, and a device. That is, examples of the article with a transparent conductive film include an element with a transparent conductive film, a member with a transparent conductive film, and a device with a transparent conductive film.

[0072] Examples of the element include a light control element and a photoelectric conversion element. Examples of the light control element include a current-driven light control element and an electric field-driven light control element. Examples of the current-driven light control element include an electrochromic (EC) light control element. Examples of the electric field-driven light control element include a PDLC (polymer dispersed liquid crystal) light control element, a PNLC (polymer network liquid crystal) light control element, and a SPD (suspended particle device) light control element. Examples of the photoelectric conversion element include a solar cell. Examples of the solar cell include an organic thin-film solar cell and a dye-sensitized solar cell. Examples of the member include an electromagnetic wave shielding member, a heat ray control member, a heater member, and an antenna member. Examples of the device include a touch sensor device, a lighting device, and an image display device.

[0073] The article with a transparent conductive film is suitable for achieving a high etching rate in the light transmissive conductive layer 20 of the transparent conductive film X included therein, and is therefore suitable for achieving high production efficiency.

[0074] Examples of the above-mentioned fixing functional layer include an adhesive layer and a bonding layer. The material of the fixing functional layer is not particularly limited as long as it has transparency and exhibits a fixing function. The fixing functional layer is preferably formed from a resin. Examples of the resin include acrylic resin, silicone resin, polyester resin, polyurethane resin, polyamide resin, polyvinyl ether resin, vinyl acetate / vinyl chloride copolymer, modified polyolefin resin, epoxy resin, fluororesin, natural rubber, and synthetic rubber. The resin is preferably an acrylic resin because it exhibits adhesive properties such as cohesiveness, adhesiveness, and moderate wettability, is excellent in transparency, and is excellent in weather resistance and heat resistance.

[0075] The adhesion functional layer (resin forming the adhesion functional layer) may contain a corrosion inhibitor to inhibit corrosion of the light-transmitting conductive layer 20. The adhesion functional layer (resin forming the adhesion functional layer) may contain a migration inhibitor (e.g., a material disclosed in JP 2015-022397 A) to inhibit migration of the light-transmitting conductive layer 20. The adhesion functional layer (resin forming the adhesion functional layer) may contain an ultraviolet absorbing agent to inhibit deterioration during outdoor use of the article. Examples of ultraviolet absorbing agents include benzophenone compounds, benzotriazole compounds, salicylic acid compounds, oxalic acid anilide compounds, cyanoacrylate compounds, and triazine compounds.

[0076] In addition, when the transparent substrate 10 of the transparent conductive film X is fixed to an article via an adhesive functional layer, the light-transmitting conductive layer 20 (including the light-transmitting conductive layer 20 after patterning) is exposed in the transparent conductive film X. In such a case, a cover layer may be disposed on the exposed surface of the light-transmitting conductive layer 20. The cover layer is a layer that covers the light-transmitting conductive layer 20, and can improve the reliability of the light-transmitting conductive layer 20 and suppress the deterioration of the function of the light-transmitting conductive layer 20 due to damage. Such a cover layer is preferably formed from a dielectric material, and more preferably from a composite material of a resin and an inorganic material. Examples of the resin include the resins described above with respect to the adhesive functional layer. Examples of the inorganic material include inorganic oxides and fluorides. Examples of the inorganic oxide include silicon oxide, titanium oxide, niobium oxide, aluminum oxide, zirconium dioxide, and calcium oxide. Examples of the fluoride include magnesium fluoride. The cover layer (a mixture of resin and inorganic material) may further contain the above-mentioned corrosion inhibitor, migration inhibitor, and ultraviolet absorbing agent. EXAMPLES

[0077] The present invention will be specifically described below with reference to examples. The present invention is not limited to the examples. In addition, the specific numerical values ​​of the blending amounts (contents), physical property values, parameters, etc. described below can be replaced with the upper limit (a numerical value defined as "equal to or less than") or lower limit (a numerical value defined as "equal to or more than") of the blending amounts (contents), physical property values, parameters, etc. corresponding thereto described in the above-mentioned "Form for carrying out the invention".

[0078] Example 1 A UV-curable resin composition containing an acrylic resin was applied to one side of a long cycloolefin polymer (COP) film (trade name "ZEONOR", thickness 40 μm, manufactured by ZEON Corporation) as a transparent resin film to form a coating film. Next, the coating film was cured by UV irradiation to form a hard coat layer (thickness 1 μm). Next, a UV-curable resin composition (composite resin composition containing zirconia particles) for forming a refractive index adjustment layer was applied to the hard coat layer to form a coating film. Next, the coating film was cured by UV irradiation to form a refractive index adjustment layer (thickness 90 nm, refractive index 1.62) on the hard coat layer. In this way, a transparent substrate having a resin film, a hard coat layer, and a refractive index adjustment layer in this order was produced.

[0079] Next, a 66 nm thick amorphous light-transmitting conductive layer was formed on the hard coat layer of the transparent substrate by reactive sputtering (film formation process). In the reactive sputtering, a sputtering film formation device (DC magnetron sputtering device) capable of performing a film formation process by roll-to-roll method was used. The sputtering film formation conditions in this embodiment are as follows.

[0080] The target used was a sintered body of indium oxide and tin oxide (tin oxide concentration: 10% by mass). A DC power supply was used as the power source for applying voltage to the target. The horizontal magnetic field strength above the target was 90 mT. The film formation temperature (the temperature of the transparent substrate on which the light-transmitting conductive layer is laminated) was 20°C. The ultimate vacuum in the film formation chamber of the device was 0.8×10 -4After evacuating the film formation chamber until the pressure reached 0.2 Pa, Kr as a sputtering gas and oxygen as a reactive gas were introduced into the film formation chamber, and the pressure in the film formation chamber was set to 0.2 Pa. The ratio of the amount of oxygen introduced to the total amount of Kr and oxygen introduced into the film formation chamber was about 2 flow %, and the amount of oxygen introduced was within region R of the resistivity-oxygen introduction amount curve as shown in FIG. 4, and the resistivity value of the formed film was 6.9×10 -4 The resistivity vs. oxygen introduction amount curve shown in Figure 4 was created by investigating in advance the dependence of the resistivity of the optically transparent conductive layer on the amount of oxygen introduced, when the optically transparent conductive layer was formed by reactive sputtering under the same conditions as above, except for the amount of oxygen introduced.

[0081] Next, the light-transmitting conductive layer on the transparent substrate was crystallized by heating in a hot air oven (crystallization step). In this step, the heating temperature was 130° C., and the heating time was 1.5 hours.

[0082] In this manner, a transparent conductive film was produced in Example 1. The light-transmitting conductive layer (thickness: 66 nm, crystalline) of the transparent conductive film in Example 1 was composed of a single Kr-containing ITO layer.

[0083] [Examples 2 and 3 and Comparative Example 1] The transparent conductive films of Examples 2 and 3 and Comparative Example 1 were each produced in the same manner as the transparent conductive film of Example 1, except for the following points.

[0084] In the film formation process, the thickness of the light-transmitting conductive layer formed was 56 nm (Example 2), 41 nm (Example 3), or 43 nm (Comparative Example 1) instead of 66 nm, and the resistivity of the formed film was 6.9×10 -4 7.4×10 instead of Ω cm -4 Ω cm (Example 2), 7.2 × 10 -4 Ω cm (Example 3) or 7.5 × 10 -4 The amount of oxygen introduced was adjusted to be Ω·cm (Comparative Example 1).

[0085] The light-transmitting conductive layer (crystalline) of each of the transparent conductive films of Examples 2 and 3 and Comparative Example 1 was composed of a single Kr-containing ITO layer.

[0086] Comparative Example 2 A transparent conductive film of Comparative Example 2 was produced in the same manner as the transparent conductive film of Example 1, except for the following points.

[0087] In the film formation process, Ar was used as the sputtering gas instead of Kr, the film formation pressure was changed from 0.2 Pa to 0.4 Pa, and the resistivity of the formed film was 6.5×10 -4 7.0×10 instead of Ω cm -4 The amount of oxygen introduced was adjusted to obtain a pressure of Ω·cm.

[0088] The light-transmitting conductive layer (thickness: 70 nm, crystalline) of the transparent conductive film of Comparative Example 2 was composed of a single Ar-containing ITO layer.

[0089] Comparative Example 3 A transparent conductive film of Comparative Example 3 was produced in the same manner as the transparent conductive film of Example 1, except for the following points.

[0090] In the film formation process, a first sputtering deposition was carried out in order to form a first layer (thickness 26 nm) on the transparent substrate, and a second sputtering deposition was carried out in order to form a second layer (thickness 4 nm) on the first layer.

[0091] The conditions for the first sputtering film formation in this comparative example are as follows: A sintered body of indium oxide and tin oxide (tin oxide concentration: 10 mass %) was used as the target. A DC power supply was used as the power supply for applying a voltage to the target. The horizontal magnetic field strength above the target was 90 mT. The film formation temperature was 20°C. The ultimate vacuum in the first film formation chamber of the device was 0.8×10 -4After evacuating the first film formation chamber until the pressure reached 0.4 Pa, Ar as a sputtering gas and oxygen as a reactive gas were introduced into the first film formation chamber, and the pressure in the film formation chamber was set to 0.4 Pa. The amount of oxygen introduced into the film formation chamber was adjusted so that the resistivity of the film formed was 6.2×10 -4 The resistivity was adjusted to Ω·cm.

[0092] The conditions for the second sputtering film formation in this comparative example are as follows: A sintered body of indium oxide and tin oxide (tin oxide concentration: 3 mass %) was used as a target. The ultimate vacuum in the second film formation chamber of the device was 0.8×10 -4 After evacuating the second film formation chamber until the pressure reached 0.2 Pa, Ar as a sputtering gas and oxygen as a reactive gas were introduced into the second film formation chamber, and the pressure in the film formation chamber was set to 0.2 Pa. In this comparative example, the other conditions of the second sputter formation were the same as those of the first sputter formation.

[0093] The light-transmitting conductive layer (thickness 30 nm, crystalline) of the transparent conductive film of Comparative Example 3 has, from the transparent substrate side, a first layer (thickness 26 nm) made of an Ar-containing ITO layer and a second layer (thickness 4 nm) made of an Ar-containing ITO layer.

[0094] Comparative Example 4 A transparent conductive film of Comparative Example 4 was produced in the same manner as the transparent conductive film of Example 1, except for the following points.

[0095] In the film formation process, Ar was used instead of Kr as the sputtering gas, and the resistivity of the formed film was 6.5×10 -4 3.1×10 instead of Ω cm -4 The amount of oxygen introduced was adjusted to obtain a conductivity of Ω·cm, and the thickness of the light-transmitting conductive layer formed was 83 nm instead of 66 nm.

[0096] The light-transmitting conductive layer (thickness: 83 nm, crystalline) of the transparent conductive film of Comparative Example 4 was composed of a single Ar-containing ITO layer.

[0097] <Thickness of Light-Transmitting Conductive Layer> The thickness of the light-transmitting conductive layer in each of the transparent conductive films in Examples 1 to 3 and Comparative Examples 1 to 4 was measured by FE-TEM observation. Specifically, first, a cross-sectional observation sample of each of the light-transmitting conductive layers in Examples 1 to 3 and Comparative Examples 1 to 4 was prepared by FIB microsampling. In the FIB microsampling method, an FIB device (product name "FB2200", manufactured by Hitachi) was used, and the acceleration voltage was set to 10 kV. Next, the thickness of the light-transmitting conductive layer in the cross-sectional observation sample was measured by FE-TEM observation. In the FE-TEM observation, an FE-TEM device (product name "JEM-2800", manufactured by JEOL) was used, and the acceleration voltage was set to 200 kV.

[0098] The thickness of the first layer of the light-transmitting conductive layer in Comparative Example 3 was measured by FE-TEM observation of a cross-sectional observation sample prepared from an intermediate product before the second layer was formed on the first layer. The thickness of the second layer of the light-transmitting conductive layer in Comparative Example 3 was determined by subtracting the thickness of the first layer from the total thickness of the light-transmitting conductive layer in Comparative Example 3.

[0099] <Specific resistance> The resistivity of the light-transmitting conductive layer was examined for each of the transparent conductive films of Examples 1 to 3 and Comparative Examples 1 to 4. Specifically, the surface resistance of the light-transmitting conductive layer was measured by a four-terminal method in accordance with JIS K 7194 (1994), and then the resistivity (Ω·cm) was calculated by multiplying the surface resistance value by the thickness of the light-transmitting conductive layer. The results are shown in Table 1.

[0100] Hall mobility and carrier density The hole mobility and carrier density of the light-transmitting conductive layer were measured for each of the transparent conductive films in Examples 1 to 3 and Comparative Examples 1 to 4. A Hall effect measurement system (product name "HL5500PC", manufactured by Bio-Rad Laboratories, Inc.) was used for this measurement. The hole mobility μ (cm 2 / V s) and carrier density n×10 19 (cm -3 ) are shown in Table 1. Table 1 also shows the ratio of n to μ (n / μ).

[0101] Etching Speed The etching rate of the light-transmitting conductive layer was examined for each of the transparent conductive films of Examples 1 to 3 and Comparative Examples 1 to 4. Specifically, for the transparent conductive films, one cycle was repeated in which the following first step, second step, and third step were carried out in this order (one cycle was repeated until etching was determined to be complete in the third step based on the criteria described below).

[0102] In the first step, the transparent conductive film was immersed in hydrochloric acid with a concentration of 7% by mass. The immersion temperature was 35°C. The immersion time was 15 seconds. In the second step, the transparent conductive film was washed with water and then dried. In the third step, the resistance between a pair of terminals separated by a distance of 15 mm (terminal resistance) was measured on the exposed surface of the light-transmitting conductive layer of the transparent conductive film using a surface resistance measuring tester. If the measured terminal resistance exceeded 50 kΩ or was not measurable, it was determined that etching was completed in the first step of the cycle to which the third step belonged. The etching rate (seconds / nm) was calculated by dividing the cumulative immersion time (etching time) of multiple first steps in multiple cycles by the thickness of the light-transmitting conductive layer. The values ​​are shown in Table 1.

[0103] <Confirmation of Kr atoms in the light-transmitting conductive layer> It was confirmed that each of the light-transmitting conductive layers in Examples 1 to 3 and Comparative Example 1 contained Kr atoms as follows. First, using a scanning X-ray fluorescence analyzer (product name "ZSX PrimusIV", manufactured by Rigaku Corporation), fluorescent X-ray analysis was repeated five times under the following measurement conditions, and the average value of each scanning angle was calculated to create an X-ray spectrum. It was confirmed that a peak appeared in the vicinity of a scanning angle of 28.2° in the created X-ray spectrum, thereby confirming that Kr atoms were contained in the light-transmitting conductive layer.

[0104] <Measurement conditions> Spectrum;Kr-KA Measurement diameter: 30mm Atmosphere: Vacuum Target: Rh Tube voltage: 50kV Tube current: 60mA Primary filter: Ni40 Scanning angle (deg): 27.0~29.5 Step(deg):0.020 Speed ​​(deg / min): 0.75 Attenuator: 1 / 1 Slit: S2 Spectroscopic crystal: LiF(200) Detector: SC PHA:100-300

[0105] [Table 1]

[0106] [evaluation] In each of the transparent conductive films of Examples 1 to 3, the light-transmitting conductive layer contains Kr, and the above-mentioned n / μ value in the light-transmitting conductive layer is equal to or greater than 4. In each of the transparent conductive films of Examples 1 to 3, a higher etching rate is realized in the light-transmitting conductive layer than in the transparent conductive film of Comparative Example 1 (wherein the n / μ value is less than 4) and the transparent conductive films of Comparative Examples 2 to 4 (wherein the light-transmitting conductive layer does not contain Kr).

[0107] Moreover, the transparent conductive films of Examples 1 to 3 (in which the light-transmitting conductive layer contains Kr) have a lower resistivity of the light-transmitting conductive layer than the transparent conductive films of Comparative Examples 2 to 4 (in which the light-transmitting conductive layer does not contain Kr). The transparent conductive films of Examples 2 and 3 (in which the light-transmitting conductive layer contains Kr and the value of n / μ is 4 or more) have a particularly low resistivity of the light-transmitting conductive layer, which is lower than the transparent conductive film of Comparative Example 1 (in which the light-transmitting conductive layer contains Kr but the value of n / μ is less than 4). [Industrial Applicability]

[0108] The transparent conductive film of the present invention can be used as a conductive film supply material for patterning transparent electrodes in various devices such as liquid crystal displays, touch panels, and optical sensors. [Explanation of symbols]

[0109] X Transparent conductive film D Thickness direction 10 Transparent base material 11 Resin film 12 Functional Layer 20 Light-transparent conductive layer

Claims

1. A transparent substrate and a light-transmitting conductive layer are provided in this order in a thickness direction, the light-transmitting conductive layer is a crystalline film and contains krypton; The light-transmitting conductive layer has a hole mobility μ (cm 2 / V·s) and carrier density n×10 19 (cm -3 ) and the ratio of n to μ is 4.4 or more and 20 or less.

2. The transparent conductive film of claim 1 , wherein the light-transmitting conductive layer contains an indium-containing conductive oxide.

3. The hole mobility is 5 cm 2 / V・s or more 40cm 2 The transparent conductive film according to claim 1 or 2, wherein the linearity is 0.1 to 1.0 V. / V·s or less.

4. The carrier density is 100×10 19 cm -3 Above 170 x 10 19 cm -3 The transparent conductive film according to claim 1 , wherein:

5. 5. The method according to claim 1, wherein the light-transmitting conductive layer is patterned. Transparent conductive film.

Citation Information

Patent Citations

  • Multiple layer modulation-doped ZnO-MgZnO transparent conductive oxide thin film

    CN101211990A

  • Manufacture of transparent conductive film

    JP1993334924A

  • Transparent conductive film and its forming method

    JP1995262829A

  • Transparent conducting film and manufacturing method therefor

    JP2011018623A

  • Transparent conductive film

    JP2014103067A